A150 ACCESS TIMES TO GASTROENTEROLOGY FOR HIGH-RISK IBD REFERRALS IN THE GREATER CALGARY REGION. (26th February 2020) - St-Pierre, J; Oshiomogho, I; Bindra, G; Kaplan, G G; Panaccione, R; Seow, C; Nasser, Y; Beck, P; Jijon, H
Abstract: Background: Delay in the diagnosis of inflammatory bowel disease (IBD) can lead to adverse outcomes. In 2006, the CAG Wait Time Consensus Group recommended that wait times for patients with symptoms highly suggestive of IBD should be seen within two weeks. In 2007, the greater Calgary region established a central access and triage system to improve access to care as well as the "High-Risk IBD clinic" (HR-IBD) to further expedite the access of patients with IBD alarm symptoms. These included diarrhea, rectal bleeding, weight loss, abnormalities in laboratory and stool investigations. Aims: The current study aimed to evaluate whether patient access to the HR-IBD clinic in the Calgary region was within recommended wait times. Methods: We conducted a cross-sectional study of charts from consented patients pulled from the EMR of five Gastroenterologists in the Calgary region that received HR-IBD referrals from Feb 2014 to Jan 2018. Of the 206 patients included, the majority were female (139 vs 65) and the mean age was 34.4 y, with no statistical difference in age between genders ( p =0.81). Data analysis was done with Stata (StataCorp 2019). Results: The mean time to initial consult was 74.8 days (median 64), whereas time to endoscopy was 85.5 days (median 77). There was no statistical difference in the mean wait times between genders. Of the patient charts reviewed, 27% of referrals had a confirmed diagnosis of IBD (CD 17%, UC 11%). Patients with a diagnosis of UC waited a mean of 60.1 days (median 60) until initial consultation and patients with a diagnosis of CD waited 77 days (median 63.5), although this was not statistically different ( p =0.27). The mean time to endoscopy for patients with UC was 77 days (median 67), and 85.4 days for patients with CD (median 78.5), again not statistically different. These wait times are below the reported wait times for all GI complaints, of 92 days from referral to consultation and 155 days from referral to procedure, as reported in the SAGE survey (2012). Although there were no differences in time to consult and endoscopy between groups, there were notable differences in alarm symptoms reported in the referral. For example, rectal bleeding was reported in 81.8% of referrals that culminated in a diagnosis of UC, as compared to 50% in CD and 47.6% of non-IBD patients. Further analysis in which alarm symptoms correlate with a final diagnosis of IBD may guide triaging of referrals to decrease the time to diagnosis. Conclusions: Timely access for consultation and endoscopy for patients presenting with high-risk features for IBD by Gastroenterology in the Calgary region remains above the CAG recommended wait times. Further correlation of high-risk features with a final diagnosis of IBD will help risk-stratify referrals in order to decrease time to IBD diagnosis. Funding Agencies: CIHRAlberta Innovates Health Solutions